2005
DOI: 10.1093/brain/awh442
|View full text |Cite
|
Sign up to set email alerts
|

Subdural recordings of the mismatch negativity (MMN) in patients with focal epilepsy

Abstract: Mismatch negativity (MMN) is elicited by discernible changes in an otherwise regular stream of auditory stimulation and reflects a pre-attentive detection mechanism. In the current study, auditory evoked potentials were recorded intracranially and electrode contacts sensitive for stimulus deviance were selected in order to further elucidate the contribution of different brain areas to MMN generation. Data were obtained from patients with frontal and temporal lobe epilepsy undergoing a presurgical evaluation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
65
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 54 publications
11
65
1
Order By: Relevance
“…Combined EEG/fMRI studies have shown in addition that activity from the inferior frontal cortex can also contribute to the MMN (Doeller et al, 2003;Rinne et al, 2005). This is in line with intracranial recordings (in presurgical patients) which have found MMN generators in secondary auditory areas (Halgren et al, 1995), in the auditory association cortex (Kropotov et al, 2000), and in the inferior frontal cortex (Rosburg et al, 2005;Marco-Pallarés et al, 2005). Thus, while one has to bear in mind that the exact location of the MMN generator may vary depending on stimulus features and on stimulus complexity (Alho, 1995;Molholm et al, 2005), the involvement of supratemporal (STG) and inferior frontal generators has been shown by a number of approaches.…”
Section: Discussionsupporting
confidence: 80%
“…Combined EEG/fMRI studies have shown in addition that activity from the inferior frontal cortex can also contribute to the MMN (Doeller et al, 2003;Rinne et al, 2005). This is in line with intracranial recordings (in presurgical patients) which have found MMN generators in secondary auditory areas (Halgren et al, 1995), in the auditory association cortex (Kropotov et al, 2000), and in the inferior frontal cortex (Rosburg et al, 2005;Marco-Pallarés et al, 2005). Thus, while one has to bear in mind that the exact location of the MMN generator may vary depending on stimulus features and on stimulus complexity (Alho, 1995;Molholm et al, 2005), the involvement of supratemporal (STG) and inferior frontal generators has been shown by a number of approaches.…”
Section: Discussionsupporting
confidence: 80%
“…Our data are in agreement with Näätänen et al (2005) that separate mechanisms account for N1 and MMN by showing that the time course of RP and MMN extends well beyond that of N1. This is also supported by human intracranial identification of separate N1 and MMN generator sites (Rosburg et al, 2005). Our data show that rapid SSA may underlie echoic memory-trace formation (see also Ulanovsky et al, 2003) by identifying an ERP component (RP), which accounts for most of the MMN memory-trace effect.…”
Section: Adaptation Effects and Mmn Generationsupporting
confidence: 79%
“…Similarly, mismatch potentials recorded from temporal (mastoid) and frontal electrodes partially may originate from different sources, despite the polarity inversion typical for a single dipole source in the superior temporal plane. This was based on studies of MMN scalp topography (Giard et al, 1990(Giard et al, , 1995Baldeweg et al, 1999Baldeweg et al, , 2002Rinne et al, 2000) and developmental changes (Gomot et al, 2000) and intracranial recordings in humans Halgren et al, 1995;Kropotov et al, 1995;Liasis et al, 2001;Rosburg et al, 2005). This dissociation was also visible here, showing ERP repetition effects in frontal but not in temporal electrodes in the passive condition.…”
Section: Neural Generators Of Rpsupporting
confidence: 63%
“…This response is interpreted by an automatic cortical change detection process, in which the difference is found between the current intensity and the representation of the regular aspects of the present auditory intensity. Rosburg et al (2005) 26 reported that MMN is obtained by means of auditory stimulation changes and reflects a pre-attention mechanism. The auditory evoked potentials were recorded in an intracranial way and sensitive contacts of electrodes for stimulus alteration.…”
Section: Mismatch Negativity (Mmn)mentioning
confidence: 99%